Kepercayaan Diri Dan Kecemasan: Bagaimana Hubungannya Terhadap Performa Pertandingan? - Julisa, Sarifah; Juita, Ardia; AF, Oca Fernandes (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2024)
One extremely significant aspect of a person's personality is their level of confidence, which stems from their experiences and their knowledge of the world. Moreover, an athlete's psychological state particularly with regard to emotions like anxiety will affect their performance in both good and bad ways. Correlational research methodology is employed in quantitative research. The study's sample consists of eight athletes from Patbanbu College who competed in the 2023 O2SN SMA Riau Province event's pencak silat branch. Other data gathering methods, including as observation, interviews, and questionnaires, might be used. Using SPSS 23, a multiple correlation analysis approach was used to analyze the study's data. According to the study's findings, there is a significant value of 0.001 < 0.05 and a link between confidence and anxiety and the performance of the pencak silat branch of the O2SN SMA event in Riau Province, with a F value of 34,389 > F table (df 2; 6) 4.21. Athletes with high levels of confidence will react to the match with confidence and good conduct, preventing or minimizing stress and worry. However, anxiety problems cause anxiety to become strong or rise in athletes with poor self-esteem, which negatively impacts the performance of Patbanbu College pencak silat athletes competing in the O2SN high school tournament in the province of Riau.